Analysis of Vocational Learning in Business Management Program Regarding The Requirements of work Competencies in Business and Industry Sector - Manopo, Meiske; Ponggohong, Laurens; Makapedua, Jacob Tatoel; Makapedua, Juliet (Universitas Diponegoro, 2023)
The current era of global economic integration undoubtedly brings consequences among the involved nations. One of the most evident consequences is the emergence of intense competition among these countries, particularly in the labor workforce. Workforce competence is crucial for businesses to remain competitive in this global competition. The knowledge and skills possessed by the workforce are inseparable from the education process. The rapid advancements of technology pose challenges for education systems to produce Human Resources (HR) capable of global engagement. Polytechnic State of Manado, as a vocational educational institution tasked with producing educated labor with global competence aligned with the needs of the business and industrial, continuously evaluates and enhances the educational processes to adapt to the dynamic industrial landscape. The analysis conducted should focus on aligning the knowledge and skills taught with the facilities available, such as the Investment Gallery Lab, Computer Lab, and Entrepreneurship Lab, to support appropriate learning implementation. Additionally, the application of teaching methods should encourage students to actively engage in the learning process. The research focus is the analysis of the learning implementation that supports achieving graduate competencies required by the industry and business world. The sub-focus is to analyze the facilities and infrastructure of laboratories in the learning process within the Business Administration department at Polytechnic State of Manado